INDONESIAN MORPHOLOGICAL INTERFERENCE IN BALINESE FOUND IN CUPAK TEKEN GRANTANG - Ni Made Verayanti Utami (SPHOTA: Jurnal Linguistik dan Sastra, 2014)
Abstract This paper entitled Indonesian Morphological Interference in Balinese Found in Cupak Teken Grantang is mainly aimed at investigating how the Indonesian morphological interference in Balinese is and the factors lead the interference. A Balinese folktale Cupak Teken Grantang is taken from serial online of Balinese folktale compilation www.satuabaliku.blogspot.com. The folktale is taken as reference in this paper because it represents the Indonesian morphological interference in Balinese. In this research the data source was collected by reading the folktale and choosing the words that represent the Indonesian morphological interference in Balinese. Then, the data was analyzed by descriptive qualitative and verification qualitative method.There are some theories used in analyzing the data, those are the theory of interference proposed by Menyuk (1971) on her book entitled The Acquisition and Development of Language, the theory of Balinese affix is proposed by Tim Penyusun Buku Tata Bahasa Baku Bahasa Bali (1996), the theory of Indonesian affix is proposed by Tim Penyusun Buku Pelajaran BIPA-FSUI (1995), and the theory for analyzing the factors lead the interference is proposed by Grosjean (1982). At last, it is found that there are three words in Balinese interfered by Indonesian affixes found and analyzed in this research. They are Balinese suffix ma-influenced by Indonesian suffix meN-, Balinese suffix pa-influenced by Indonesian suffix peN-, and Balinese affix ka-…-an influenced by Indonesian affix ke-…-an. The interferences in this research are caused by hypercorrection and influence of the other language. The hypercorrection looked on word-forming error that is might caused by the lack of knowledge of the writers and the morphological interference in Balinese influenced by Indonesian morphological form. Keywords: interference, morphological, affix